Assessment of response to neoadjuvant radiochemotherapy with F-18 FLT and F-18 FDG PET/CT in patients with rectal cancer - Rendl, Gundula; Rettenbacher, Lukas; Holzmannhofer, Johannes; Datz, Lidwina; Hauser-Kronberger, Cornelia; Fastner, Gerd; Öfner, Dietmar; Sedlmayer, Felix; Pirich, Christian (Annals of nuclear medicine, 2015)
Objective The comparison of 2-deoxy-2-[18F]fluoro- d -glucose (F-18 FDG) and 3′-deoxy-3′-[18F]fluorothymidine (F-18 FLT) imaging in patients with rectal cancer before and after neoadjuvant radiochemotherapy (RCT) in relation to histopathology and immunohistochemistry obtained from surgery. Methods 20 consecutive patients (15 m, 5 f), mean age of 65 ± 10 years were included into this prospective study with a mean follow-up of 4.1 ± 0.8 years. Results Among histopathological responders ( n = 8 out of 20), posttreatment F-18 FLT and F-18 FDG scans were negative in 75 % ( n = 6) and 38 % ( n = 3), respectively. The mean response index (RI) was 61.0 % ± 14.0 % for F-18 FLT and 58.7 % ± 14.6 % for F-18 FDG imaging. Peritumoral lymphocytic infiltration (CD3 positive cells) was significantly related to posttreatment SUV max in F-18 FDG but not F-18 FLT studies. Conclusion A significant decrease of SUV max in F-18 FDG and F-18 FLT studies could be seen after RCT. Negative posttreatment F-18 FLT studies identified more histopathological responders.